Community and connectedness in online higher education: a scoping review of the literature. Issue 1 (2nd January 2021) - Trespalacios, Jesús; Snelson, Chareen; Lowenthal, Patrick R.; Uribe-Flórez, Lida; Perkins, Ross
ABSTRACT: Community and connectedness are important concepts in online higher education. However, researchers debate how they are defined, operationalized, or enacted in practice. A scoping study was conducted to review the research literature on the extent, range, and nature of research in community and connectedness in online higher education. A total of 66 studies published from 2001 through 2018 were identified for review. The findings illustrate how research on community and connectedness has focused on areas such as course design, technology tools, faculty, and students as well as highlight the important role these concepts have played in the last two decades in online higher education. The gaps in the literature suggest a need to further investigate the role community and connectedness play in different types of programs and other roles that faculty, staff, and students could play to foster these concepts.